Análisis de riesgo de crecidas en la cuenca del río Guare, Valle de San José, Santander (2023)
This study seeks to establish the level of risk to flood events, for this topographic information obtained from the NASA ALOS PALSAR mission, IDEAM hydrometeorological information and IGAC cartographic data were used, which were processed in the free-use geographic information in QGIS and in Microsoft Excel spreadsheets. After their respective processing, morphometric and hydrological indices were calculated, which were compared with results obtained by researchers from different parts of the world who carried out similar investigations, based on their experience, an analysis of the results obtained was generated based on the possibility of presenting an instantaneous discharge of water within the sub-basin and their respective concentration and delay times.